2018
DOI: 10.3389/fphys.2018.00438
|View full text |Cite
|
Sign up to set email alerts
|

Cue-Induced Ethanol Seeking in Drosophila melanogaster Is Dose-Dependent

Abstract: Alcohol use disorder generates devastating social, medical and economic burdens, making it a major global health issue. The persistent nature of memories associated with intoxication experiences often induces cravings and triggers relapse in recovering individuals. Despite recent advances, the neural and molecular mechanisms underlying these memories are complex and not well understood. This makes finding effective pharmacological targets challenging. The investigation of persistent alcohol-associated memories… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 59 publications
2
31
0
Order By: Relevance
“…Our runway-based operant administration data here reveal that flies willingly self-administer ethanol following initial exposure, despite finding the ethanol aversive. Interestingly, the ethanol dose that induced the most striking behavioral responses in the runway task is similar to the one that induced the highest appetitive response in a Pavlovian odor-ethanol association memory task [15]. We found that within each day, initial ethanol administration induced early bouts of thrashing behavior, followed by decreasing velocity and increased levels of pausing, cumulatively supporting aversion.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Our runway-based operant administration data here reveal that flies willingly self-administer ethanol following initial exposure, despite finding the ethanol aversive. Interestingly, the ethanol dose that induced the most striking behavioral responses in the runway task is similar to the one that induced the highest appetitive response in a Pavlovian odor-ethanol association memory task [15]. We found that within each day, initial ethanol administration induced early bouts of thrashing behavior, followed by decreasing velocity and increased levels of pausing, cumulatively supporting aversion.…”
Section: Discussionsupporting
confidence: 51%
“…Flies exhibit preference for an odor associated with moderate dose ethanol intoxication one to seven days after pairing [14,15]. However, this Pavlovian assay lacks the tracking resolution to quantify behavior during ethanol administration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Training was performed in the dark with minimal red-light illumination and was preceded by a 20-minute habituation to the training chambers. Training chambers were constructed out of PlexiGlas (30 x 15 x 15 cm) (for details please refer to (Nuñez, Azanchi et al 2018)). During habitation, humidified air (flow rate: 130) was streamed into the chambers.…”
Section: Behavioral Experimentsmentioning
confidence: 99%
“…Drosophila exhibit sophisticated behaviors in response to changes in their environment, including formation of appetitive memories for food associated with environmental cues (Waddell 2010, Kahsai and Zars 2011, Schleyer, Saumweber et al 2011, Herrero 2012, Fernandez and Kravitz 2013, Heisenberg 2015, Owald, Lin et al 2015. Drosophila also form appetitive memories for the pharmacological properties of alcohol (Kaun, Azanchi et al 2011, Nuñez, Azanchi et al 2018. These alcohol memories are persistent and impel flies to walk over a 120V electric shock in the presence of associated cues.…”
Section: Introductionmentioning
confidence: 99%